Culturally Responsive Teaching with Adult Language Learners - Christy M. Rhodes (Adult Education Research Conference, 2015)
This study examined how frequently adult education English for Speakers of Other Languages (ESOL) and English for Academic Purposes (EAP) teachers in Florida used specific culturally responsive teaching practices and how important they believed those practices were to their teaching. Using Ginsberg and Wlodkowski’s Motivational Framework for Culturally Responsive Teaching, an online survey of 17 teaching practices was developed, validated, and administered to 143 adult ESOL and EAP teachers in Florida. This article describes the findings of this study, examining which practices were used with the highest and least frequency, as well as the practices described as most and least important to their teaching.
Keywords: English as a second language; adult learning; motivational framework for culturally responsive teaching